Alkali Solubilized Nickel(II)-Dimethylglyoxime as a New Redox Indicator - Muralikrishna, U.; Sivaramakrishna, A. (Asian Journal of Chemistry, 2010)
Alkali solubilized nickel(II)-dimethylglyoxime has been proposed as a new redox indicator in ferricyanide oxidimetry. The determination of hydroxylamine and semicarbazide is carried out with a pooled standard deviation of 0.09 and 0.11 mg respectively.